A Methodological Proposal for the Analysis of Lighting the House Building Façades. - Castro Noblejas, Hugo; Sortino-Barrionuevo, Juan Francisco; Gumiel Muñoz, Darío; Mérida-Rodríguez, Matías Francisco (MDPI, 2021)
Natural lighting is a fundamental element in the habitability of dwellings. However, it is still difficult to calculate its effect on the façades of the buildings in detail, due to the morphological complexity of the property itself, as well as the environment that surrounds it. This study provides a methodological proposal that uses pre-existing open data to extrude buildings by using a GIS procedure. Based on three selected real estate properties with different characteristics in the city of Marbella (Spain), the hours of sunlight received by each building’s façade are calculated, taking into account the digital land model and the digital surface model of the area. The results confirm the usefulness of the method to measure and analyze differences in luminosity between buildings with similar urban characteristics and their surroundings, as well as to record the differences in luminosity between floors and the orientations of the same building at several heights. The methodological proposal opens a path for many applications related to energy efficiency, housing conditions, and property valuation.
Keywords: Iluminación natural; Urbanismo - Aspectos ambientales; GIS; Building extrusion; Façades; Habitability; Solar lighting; Urban spaces